Extracellular vesicles and exosomes generated from cystic renal epithelial cells promote cyst growth in autosomal dominant polycystic kidney disease - Hao Ding (Nature Portfolio, 2021)
Autosomal dominant polycystic kidney disease is characterized by the formation of cysts in the kidney. Here the authors show that cystic extracellular vesicles/exosomes play a critical role in regulating the biology and function of adjacent cells, including renal epithelial cells, fibroblasts and macrophages, and contribute to renal cyst growth.